Analysis of the performance training program of the base macrocycle of the annual cycle - Dragu, M.; Solonenco, G. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2017)
Athletic swimming is part of the individual sporting industries characterized by the mechanical action of cycling through intense psychic participation and by cumulative stresses and impacts from a morpho-functional and motive point of view. Over the years, from one eventto another, swimming has seen a steady increase in results. This development resulted from the continuous renewal of 40-50% annual performance, both nationally and globally. Also, the increase in the number of participants in international competitions has led to an increase in swimming performance. Any success strategy is based on a very accurate, well-grounded and viable principle. It should also be emphasized that in order to create a climate of great performance, the elite group of seniors will be open only to those who are committed to submitting to a program in order to complete their training. Each member of this group will be asked to work for the purpose of perfection, be it technique, intensity or any other field of training. The purpose of training programs is to produce metabolic, physiological and psychological adaptations to allow swimmers to swim better. Adaptations are actually the changes that are the result of the body's response to training. Planning the training in a macrocycle was approached methodically and scientifically by a multitude of practitioners and theoreticians, who present detailed elaborations on the performance objectives, the methods and means used, the volume and the intensity of the training effort applied in the training of the swimmers performance level.